A personagem feminina subalterna na ficção de Nélida Piñon e Francisco Dantas - Fonsêca, Joseana Souza da (2010)
This paper proposes a comparative analysis of the female characters in the novels Caetana s sweet song (1987), of Nélida Piñon, and Cartilha do Silêncio (1997), of Francisco Dantas, through a sociocultural approach. We support the hypothesis that despite the woman in these works, she passes through border areas where oppression and freedom confused each other, many times she is submitted to way of life the patriarchal society. Our aim is to identify what mechanisms of the power that encompass the subaltern character as for gender / sexuality and social class aspect. In the Caetana s sweet song we give priority to the study of prostitutes: Gioconda, Diana, Palmira and Sebastiana, without leaving aside the actress mambembe Caetana. In Cartilha do Silêncio, we emphasize the subordinate place of Arcanja, a poor niece of the rich patriach Romeu Barroso, to Avelina, wife of household Barroso family, Mané Piaba, and D. Senhora, the bourgeois that has her sexuality repressed by her husband. Theoretically, we follow the guidelines that power and oppression are part of the devices of social control according to Michel Foucault. The subaltern identities are studied through sociological proposal that say all identity is mobile and flexible according to Stuart Hall and Zygmunt Bauman. Within the Brazilian literary criticism about the representation of female characters, we follow the guidelines of the studies of Elódia Xavier and Regina Dalcastagnè. Teaching purposes, this dissertation is divided into four chapters. In the first, we situate the place of Nélida Piñon‟s and Francisco Dantas‟s work and we point out the main characteristics of their female characters. In the second, we developed the concept of subaltern and oppression from the devices of gender, class and sexuality. In the third, we analyze how the discourse of the subaltern woman is constructed. In the last chapter, we add the space as an indicator of the condition of the subordinate characters, with emphasis on the study of heterotopias, spaces of crisis and construction of new identities. Thus, this research maps the main characteristics of the subaltern female characters in Nélida Piñon‟s and Francisco Dantas‟ fiction.